The amazing flight of Darius Frobisher - Harley, Bill, 1954- (Peachtree Publishers, 2006)
When his adventurous father disappears during a hot-air balloon flight, ten-year-old Darius is torn away from his beloved housekeeper and sent to live with an obnoxious aunt until a strange bicycle repairman with a secret changes his life.